Heroes, idols, and youth influencers: Cultural industries and identity models in TikTok - Lacasa, Pilar; Carbonell-Bernal, Noelia; Duran-Bonavila, Silvia; Contreras-Pulido, Paloma (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This study explains on how the TikTok platform can contribute to developing different identity models among teenage fans mediated by cultural industries. The theoretical models are those that focus on popular culture (Fiske, 1989) and, more recently, in the TikTok study (Abidin, 2021). The methodology combines big and small data analysis, inspired by the content analysis techniques, and looking at multimodal discourses. The results show different dimensions from which cultural industries build the identity of heroes, idols, or influencers. The focal points of the conclusions are the challenges posed to research by studying this social network.